Two Novel Mutations (c.883-4_890del and c.1684C>G) of WDR62 Gene Associated With Autosomal Recessive Primary Microcephaly: A Case Report - You Gyoung Yi; You Gyoung Yi; Dong-Woo Lee; Jaewon Kim; Ja-Hyun Jang; Ja-Hyun Jang; Sae-Mi Lee; Sae-Mi Lee; Dae-Hyun Jang (Frontiers Media S.A., 2019)
Background: Autosomal recessive primary microcephaly (Microcephaly Primary Hereditary, MCPH) is a rare disorder, affecting 1 in 10,000 children in areas where consanguineous marriages are common. WDR62 gene mutations are the second most common cause of MCPH. Herein, we report a case of primary microcephaly caused by two novel WDR62 mutations, which is, to our knowledge, the first such case report in East Asia.Case presentation: A 6-year-old girl visited our outpatient clinic as a result of microcephaly and delayed development. The patient was born at 36 weeks 4 days through cesarean section. Her birth weight was 1.8 kg (<1st percentile), and she was noted to have microcephaly (head circumference at birth was 28 cm, <−3SD). On examination, delayed speech development and microcephaly with an occipitofrontal head circumference of 43.5 cm (<−3SD) were noted. The patient's gross and fine motor development was normal. Her intelligence quotient was 43 (<0.1 percentile), the same as a 27-month-old child, and her social intelligence quotient was 76.92. Brain imaging revealed simplified gyral patterns of the cerebral cortex; however, laboratory findings, including organic acids, were normal. Multiplex ligation-dependent probe amplification technique for microdeletion syndrome and chromosomal microarray, showed no abnormality. Clinical exome sequencing test revealed two novel heterozygous variants in the WDR62 gene at two different sites: in the boundary of intron 7 and exon 8 (NM_001083961.1: c.883-4_890del) and in exon 13 (NM_001083961.1: c.1684C>G). The patient's parents were identified as heterozygous carriers for each variation.Conclusion: We report on two novel heterozygous mutations in East Asia. Our data expand the understanding of WDR62 mutations.